2017
DOI: 10.1111/dom.12961
|View full text |Cite
|
Sign up to set email alerts
|

Consistent findings in glycaemic control, body weight and hypoglycaemia with iGlarLixi (insulin glargine/lixisenatide titratable fixed‐ratio combination) vs insulin glargine across baseline HbA1c, BMI and diabetes duration categories in the LixiLan‐L trial

Abstract: AimsTo assess the impact of baseline characteristics on clinical outcomes in the LixiLan‐L trial, a randomized open‐label trial designed to evaluate the efficacy and safety of iGlarLixi, a novel fixed‐ratio combination of insulin glargine 100 U (iGlar) plus lixisenatide, in comparison with iGlar over 30 weeks in a population of patients with type 2 diabetes mellitus (T2DM) inadequately controlled on a previous regimen of basal insulin alone or in combination with 1 or 2 oral glucose‐lowering drugs.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
3
23
1
1
Order By: Relevance
“…Outcomes at Week 26 were included as potential predictors in this analysis because the definition of response was linked to achievement of the HbA1c goal (<7.0% [<53 mmol/mol]) at Week 26, the end of the core treatment period. In previous studies, baseline characteristics such as HbA1c were found to be strong predictors of response in some instances, although not consistently . In the current model, response at Week 26 was a stronger predictor than any baseline characteristics tested.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Outcomes at Week 26 were included as potential predictors in this analysis because the definition of response was linked to achievement of the HbA1c goal (<7.0% [<53 mmol/mol]) at Week 26, the end of the core treatment period. In previous studies, baseline characteristics such as HbA1c were found to be strong predictors of response in some instances, although not consistently . In the current model, response at Week 26 was a stronger predictor than any baseline characteristics tested.…”
Section: Resultscontrasting
confidence: 60%
“…In previous studies, baseline characteristics such as HbA1c were found to be strong predictors of response in some instances, 14,15 although not consistently. [16][17][18][19] In the current model, response at…”
Section: Resultsmentioning
confidence: 99%
“…26 Patients treated with iGlarLixi showed reductions in HbA 1c of -1.1% and with iGlar of -0.6%. A higher percentage of patients achieved the HbA 1c target level of <7% (P < 0.0001): 55% of iGlarLixi patients reached HbA 1c <7% compared with 30% of iGlar patients.…”
Section: Lixisenatide/insulin Glargine Coformulationmentioning
confidence: 90%
“…Mean body weight decreased in iGlarLixi recipients but increased in insulin glargine recipients (between‐group difference, 1.4 kg; P < 0.0001), and the number of hypoglycaemic events was similar in the two groups 53. In both studies, the improvement in glycaemic control with iGlarLixi vs the individual therapies was consistent regardless of baseline HbA 1c , BMI or diabetes duration 54, 55.…”
Section: Fixed‐ratio Formulationsmentioning
confidence: 84%